2013
DOI: 10.1039/c2sm27515e
|View full text |Cite
|
Sign up to set email alerts
|

Self-healing hydrogels formed in catanionic surfactant solutions

Abstract: Physical gels with remarkable properties were obtained by copolymerization of acrylamide with the hydrophobic monomer stearyl methacrylate (C18) in a micellar solution of cetyltrimethylammonium bromide (CTAB) containing up to 15 mol% sodium dodecyl sulfate (SDS). The addition of SDS causes the CTAB micelles to grow and thus enables solubilization of C18. The gels exhibit time-dependent dynamic moduli, high elongation ratios at break (1800-5000%), and self-healing, as evidenced by rheological and mechanical mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
78
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 88 publications
(81 citation statements)
references
References 57 publications
(75 reference statements)
0
78
1
Order By: Relevance
“…The swelling kinetics of hydrophobically modified nonionic hydrogels such as HM PAAm and HM poly(N,N-dimethylacrylamide) (PDMA) prepared in salt solutions of SDS, CTAB, or CTAB-SDS are similar to those illustrated in Fig. 7 [37,41]. In contrast, HM PAAc hydrogels formed in SDS solutions exhibit high swelling ratios in water because of the osmotic pressure of the AAc counterions [39].…”
Section: Swelling Propertiesmentioning
confidence: 89%
See 4 more Smart Citations
“…The swelling kinetics of hydrophobically modified nonionic hydrogels such as HM PAAm and HM poly(N,N-dimethylacrylamide) (PDMA) prepared in salt solutions of SDS, CTAB, or CTAB-SDS are similar to those illustrated in Fig. 7 [37,41]. In contrast, HM PAAc hydrogels formed in SDS solutions exhibit high swelling ratios in water because of the osmotic pressure of the AAc counterions [39].…”
Section: Swelling Propertiesmentioning
confidence: 89%
“…Mixtures of the anionic surfactant SDS and the cationic surfactant CTAB form mixed micelles in both SDS-rich and CTAB-rich solutions, whereas between these compositions, vesicles and formation of a 1:1 precipitate are observed [76][77][78][79]. It was shown that the correlation length of 0.24 M CTAB-SDS increases from 0.4 to 2.5 nm as the SDS content of the surfactant mixture is increased from 0 to 15 mol%, leading to increased solubility of the hydrophobic monomer C17.3M in the micellar solution [37].…”
Section: Preparation Of Hydrophobically Modified Hydrogelsmentioning
confidence: 92%
See 3 more Smart Citations